The effect of aspect ratio and volume fraction on mechanical properties of steel fibre-reinforced oil palm shell concrete - Yap, Soon Poh; Alengaram, U. Johnson; Jumaat, Mohd. Zamin (Journal of Civil Engineering and Management, 2016)
The utilization of oil palm shell (OPS) as a replacement for conventional coarse aggregate produces a greener structural lightweight aggregate concrete (LWAC). Steel fibres enhance the mechanical properties of LWAC including OPS concrete (OPSC). This paper reports on the influence of the aspect ratio (l/d) and volume fraction (Vf) of hooked end steel fibres in oil palm shell fibre-reinforced concrete (OPSFRC). The fresh and hardened concrete properties, including ultrasonic pulse velocity (UPV) and post-failure compressive strength (PFCS) of ten mixes with three each for l/d (55, 65 and 80) and Vf (0.25%, 0.5% and 0.75%) are investigated. The mix with an l/d of 65 produced the highest values of slump, density, and compressive strength. The enhancement in the splitting tensile strength of 83% compared to the control mix was obtained for the mix with the highest l/d. Generally, the increase in Vf from 0.25% to 0.75% improved the mechanical properties. The UPV results indicated that all OPSFRC and PFCS of 66–70% obtained were of good quality.First published online: 24 Aug 2015